Fictionality - Petroski, Karen (Milton Park, Abingdon Routledge, 2023)
Does fiction enhance reality, or threaten our sense of what is real? What, if anything, is special about experiencing fictional works and worlds? Today we speak casually of parallel universes and virtual reality; how much do we really know about what these phenomena involve?

In Fictionality, Karen Petroski explains how philosophers and literary theorists have approached these questions in the Western literary tradition, from Greek antiquity to the present day. The book introduces readers to both long-running and contemporary debates about:

•The value and dangers of engagement with fiction
•The origins of fictional artworks, especially literary works, in Western literature
•The role played by imagination in engaging with fiction
•The peculiarities of fictional "worlds"
•The structure of linguistic reference within fictional artworks
•The functions of fictionality in non-linguistic artworks such as film and television
•The role played by fictionality outside artworks, for example, in philosophy, law, and politics

Fictionality offers an accessible and comprehensive introduction to this field of increasing critical and theoretical interest. Bringing together theoretical insights from a variety of perspectives, it will be an essential resource for anyone studying fictionality. -- Provided by publisher.
Perspectives on fictionality -- Starting points -- Seeing as -- Other worlds -- Reference -- Beyond text -- Beyond art.
Includes bibliographical references and index
Keywords: Fiction -- History and criticism -- Theory, etc..; Fictions, Theory of